2015
DOI: 10.1124/dmd.115.064345
|View full text |Cite
|
Sign up to set email alerts
|

Danazol Inhibits Cytochrome P450 2J2 Activity in a Substrate-independent Manner

Abstract: Cytochrome P450 2J2 (CYP2J2) is an enzyme responsible for the metabolism of endogenous substrates including arachidonic acid, as well as therapeutic drugs such as albendazole, astemizole, ebastine, and terfenadine. Selective inhibitors of CYP2J2 are essential for P450 reaction phenotyping studies. To find representative CYP2J2 index inhibitors, we evaluated the inhibitory potential of danazol, hydroxyebastine, telmisartan, and terfenadone against CYP2J2 activity for four representative CYP2J2 substrates (alben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…There was no interference detected by other probe substrates or their metabolites at the retention times of interest for any metabolite SRM channel. In the case of acetaminophen and 6β‐hydroxytestosterone, three peaks were observed in the microsomal incubation, in line with previous reports (Joo, Lee, Lee, & Liu, ; Lee et al, ; Lee et al, b; Min et al, ; Pillai, Strom, Caritis, & Venkataramanan, ). These peaks with a retention time of 3.2 and 5.1 min, respectively, were identified as acetaminophen and 6β‐hydroxytestosterone by comparison with the retention time of authentic standards.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…There was no interference detected by other probe substrates or their metabolites at the retention times of interest for any metabolite SRM channel. In the case of acetaminophen and 6β‐hydroxytestosterone, three peaks were observed in the microsomal incubation, in line with previous reports (Joo, Lee, Lee, & Liu, ; Lee et al, ; Lee et al, b; Min et al, ; Pillai, Strom, Caritis, & Venkataramanan, ). These peaks with a retention time of 3.2 and 5.1 min, respectively, were identified as acetaminophen and 6β‐hydroxytestosterone by comparison with the retention time of authentic standards.…”
Section: Resultssupporting
confidence: 90%
“…Ideally, the P450 enzyme inhibition assay obtained from the cocktail incubation should yield the same results as would be obtained from individual incubations (Lee et al, b; Li et al, ). The IC 50 values of cocktail incubation were comparable to those obtained from individual incubations (Table and Figure ), ranging from 0.80 to 1.26, and a high correlation of IC 50 values was found between the individual and cocktail assays (r 2 > 0.99; Figure b), indicating that IC 50 values could be obtained accurately over a wide concentration range.…”
Section: Discussionmentioning
confidence: 99%
“…Telmisartan and flunarizine with K i values of 0.42 and 0.94 mM, respectively, could be used as moderately selective CYP2J2 inhibitors, but both compounds also inhibit CYP2C9 and CYP2D6 with IC 50 values of 4.78 and 7.89 mM, respectively (Ren et al, 2013), therefore demonstrating only a greater than 10-fold selectivity when evaluated against five major P450 isoforms (CYPs 1A2,2C9,2C19,2D6,and 3A). Danazol also showed no more than 15-fold selectivity for CYP2J2 when tested against these five P450 isoforms, although it noncompetitively inhibited CYP2J2-mediated astemizole O-demethylation activity (IC 50 = 0.07 mM) (Lee et al, 2015). Additionally, the selectivity measured did not take into consideration other minor but important P450 isoforms, such as CYP2A6, CYP2B6, CYP2C8, and CYP2E1.…”
Section: Resultsmentioning
confidence: 90%
“…Danazol (Lee et al, 2015) and telmisartan (Ren et al, 2013) showed 15-and 10-fold selectivity for CYP2J2 inhibition, respectively. To evaluate the selectivity of the tested inhibitors for CYP2J2, we examined the inhibitory activities of four LKY compounds against nine different P450 isoforms, including CYPs 1A2, 2A6, 2B6, 2C8, 2C9, 2C19, 2D6, 2E1, and 3A, in 0.25 mg/ml HLMs, under conditions common in phenotyping experiments.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation